EGFR targeted Mn-doped ZnO fluorescent nanocrystals for cancer theranostic application. (March 2021) - Misra, Ranjita; Das, Manasi; Biswas, Pronama; Nanda, Anima
Graphical abstract: Abstract: A combination of diagnosis and therapeutic treatment protocols leads to the successful management of cancer. In this context, improved diagnostic methods are needed for early cancer detection. Moreover, traditional cancer chemotherapy protocols are limited due to non-specificity and serious side effects. In the present work, we developed Mn-doped ZnO nanocrystals to manifest simultaneous drug delivery and diagnosis. Characterization results demonstrated that the synthesized nanocrystals are of nanometer range and also exhibit fluorescence property which is confirmed from fluorescence spectrophotometer and confocal microscopic study results. Cytotoxicity effects in drug resistant MCF-7 cell line showed that the nanocrystals are non-toxic up to certain concentrations, and induces toxicity at higher concentrations. However, the toxic effect of the nanocrystals was eliminated by coating a polymer on the surface of the nanocrystals. For targeted delivery, the epidermal growth factor (EGFR) antibody was surface conjugated on polymer-coated nanocrystals and the uptake of these nanocrystals was demonstrated in a drug resistant breast cancer cell line. Results depicted a higher uptake of the antibody conjugated nanocrystals compared to the unconjugated counterpart. Thus, the results suggest the potential use of EGFR conjugated Mn-doped ZnO nanocrystals in various biomedical applications, particularly in cancer diagnosis, imaging and therapy.